Toxoplasma gondii seroprevalence in the endangered Australian sea lion (Neophoca cinerea) - Lindsay, Scott A.; Caraguel, Charles G. B.; O’Handley, Ryan; Šlapeta, Jan; Gray, Rachael (Frontiers in Marine Science, 2022)
Toxoplasma gondii is a ubiquitous parasite increasingly detected in marine mammals and suspected to contribute to limited recovery of endangered populations. This study reports on the exposure of the Australian sea lion (Neophoca cinerea) to this protozoon using archived adult and pup sera from three island colonies in South Australia. Modified agglutination testing (MAT) detected a seroprevalence of 30.4% (95% CI 13.2-52.9: n = 23) and high antibody titers (512 to > 2048 IU/ml) in adult females (median age 9.5 y, range 5.5-14.5 y) at Dangerous Reef, a felid-free island. Antibodies weren’t detected in any surveyed pup (97.5% CI 0.0-2.0%, n = 184) at two felid-free islands (Dangerous Reef: n = 21; Olive Island: n = 65), nor at Kangaroo Island (n = 98), which has a high-density feral cat population. Kangaroo Island pups of known age were 7-104 d old, while standard length and bodyweight comparison suggested younger and older pup cohorts at Dangerous Reef and Olive Island, respectively. This study provides the first quantification of disease risk in this endangered species from T. gondii exposure. The absence of detectable pup seroconversion supports the lack of detectable congenital transmission, maternal antibody persistence or early post-natal infection in the sampled cohort yet to commence foraging. An extended serosurvey of N. cinerea colonies is recommended to confirm the hypothesis of predominantly forage-associated exposure to T. gondii in this species. Findings have implications for parasitic disease risk in wildlife inhabiting Australia’s islands and for the feral cat control program on Kangaroo Island.